Atmospheres and Oceans of Terrestrial Planets-II - Liu, Lin-gun (European Journal of Applied Sciences, 2026)
Both Venus and Mars most likely retain their proto-atmospheres which comprise more than 95% CO2 plus a few percent of N2. Mercury being so small and so close to the Sun for so long has only trace amounts of O2 and Na. This might imply that its rocky parts (crust + mantle) became thinner and thinner with time due to sublimation. The Earth’s CO2-rich proto-atmosphere was removed by a large quantity of supercritical H2O released from the Moon-making giant impact process. The supercritical H2O released from this impact reacted with Earth’s CO2-rich proto-atmosphere to form a supercritical H2O-CO2 mixture which yielded the hot and soda indigenous ocean when the Earth’s surface temperature cooled down to 450 300 oC. The Earth, however, retains N2 from her proto-atmosphere. The ancient Martian oceans, on the other hand, might be derived from the entrapped magma oceans via a degassing process when the Martian surface temperature cooled much below 100 oC.